Comparative Study of the Effect of Locally Made Beer (Burukutu and Pito) and Star Lager Beer on Liver Function Parameters - Ahmed, Maryam Usman; Wahedi, Lumayu Alexander; Abdulfatai, Ayinla Abayomi; Titus, Diowato; Aliyu, Kamaludden (African Journal of Biochemistry and Molecular Biology Research, 2025)
Alcohol consumption has a long history in human existence and is implicated as one of the major risk factors in the development of liver diseases. The comparative impact of locally made (burukutu and pito) sorghum-based beer and Star Larger beer on the liver biomarkers of albino rats was investigated. 35 albino rats were grouped into 7 groups of 5 rats each. Group one served as the control group and received only distilled water. Group 2 and 3 received 10 and 20 mL/kg b.wt of pito, groups 4 and 5 received 10 and 200 mL/kg b,wt of burukutu, while group 6 and 7 received 10 and 20 mL/kg of Star Larger beers, respectively, for 21 days after which the liver function parameters were assessed. There was a significant decrease (p<0.05) in albumin level of the treatment groups when compared with the control group. Bilirubin and ALP showed no significant difference (p<0.05) from the control group. There was no significant difference (p<0.05) in ALT levels of burukutu and Start Larger when compared with the control group, however, the groups treated with pito showed a significant increase (p<0.05) when compared with the control group. There was a significant increase (p<0.05) in all the treatment groups when compared with the control group, where group 3, which was treated with the higher dose of pito (20 mL/kg b.wt.) had the highest significant increase(p<0.05). albumin levels of the treatment groups showed a significant decrease (p<0.05) when compared with the control group. The three beers compared are toxic to the liver, with pito having the greatest toxicity.